2017
DOI: 10.1111/jgs.14794
|View full text |Cite
|
Sign up to set email alerts
|

Physical Abuse of Elderly Adults: Victim Characteristics and Determinants of Revictimization

Abstract: Better screening that connects victims of abuse with community services, police action, and alternative residential options is important in reducing the risk of revictimization and connecting individuals with resources that can improve their safety at home, regardless of whether it is in the community or a residential facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 48 publications
5
20
0
7
Order By: Relevance
“…Most were married or widowed, and more than half had completed elementary school. Similar results were found in investigations of cases of recurrent elder abuse in Chicago [9] and Virginia [10]. This is a profile that has been found in several studies analyzing this phenomenon [16,18,20,21,22].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Most were married or widowed, and more than half had completed elementary school. Similar results were found in investigations of cases of recurrent elder abuse in Chicago [9] and Virginia [10]. This is a profile that has been found in several studies analyzing this phenomenon [16,18,20,21,22].…”
Section: Discussionsupporting
confidence: 87%
“…This corroborates the findings of a study conducted in the United States, which investigated a sample of cases of older adult maltreatment and found that, in 14% of cases, the maltreatment was ongoing [10]. Likewise, a retrospective analysis of physically abused older patients in five large hospitals in Chicago found that 52.3% had a history of polyvictimization [9].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations